When Justice Fails: Class Struggle and Violence in Kendrick Lamar’s XXX. through a Marxist Lens - Joice Anita Siburian; T. Thyrhaya Zein; Yulia Rahma Silalahi; Priskila Anggi Marpaung; Rolan Siallagan; Yosia Situmorang (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study examines Kendrick Lamar’s song XXX. from the album DAMN. (2017) through a Marxist literary perspective to explore the representation of class struggle, violence, and social inequality in contemporary hip-hop music. While previous studies have primarily focused on race and identity in hip-hop, limited attention has been given to the intersection of social class and violence within specific musical texts. Using a qualitative research design, the study analyzes selected lyrics as cultural texts that reflect power relations, ideology, and institutional failure. The findings reveal that violence in XXX. is portrayed not merely as an individual reaction but as a consequence of structural inequality, limited access to justice, and class oppression. Furthermore, the song exposes ideological contradictions within capitalist society and critiques the failure of institutions to protect marginalized communities. The study concludes that hip-hop functions as an influential medium of social criticism, highlighting systemic injustice and the need for greater social equity and institutional accountability. Keywords: Marxism, class struggle, social inequality, violence, ideology, hip-hop, Kendrick Lamar,XXX., systemic injustice.